PEMBINAAN GENERASI MUDA PEDULI LINGKUNGAN MELALUI GERAKAN LAUDATO SI’ INDONESIA - Saptadi, Norbertus Tri Suswanto; Grace Theresia Pontoh (Jurnal Bakti Masyarakat Indonesia, 2025)
Developing a young generation who cares about the environment is both a challenge and a necessity in the modern era. The Indonesian Laudato Si' movement is present as a concrete form of internalizing integral ecological values as stated in the encyclical Laudato Si' by Pope Francis. PkM aims to form a young generation of churches who have environmental awareness, provide a theological understanding of human responsibility towards the natural world, train the young generation to take an active role in environmental conservation, and instill Christian values in protecting and caring for the environment. The PkM method consists of preparation and coordination, socializing the Laudato Si' Movement, building ecological awareness, practicing waste management, cleaning the surrounding environment, and distributing questionnaires. Community service activities in an effort to develop young people who care about the environment through assessment through questionnaire results in the form of "knowing about the Laudato Si movement" by 52 (74.4%) participants, "strongly agree with the Laudato Si movement" by 60 (86.6%) participants, "agree with Laudato Si' as a Christian Leadership Guide for Environmental Sustainability" by 52 (73.6%) participants, "agree to develop a young generation of the Church who cares about the environment" by 53 (75.2%) participants, and "Agree with the implementation of the Laudato Si' Movement" by 54 (76.0%) participants. The leading suggestions that can be given based on the results of the highest scores in distributing questionnaires to participants as follow-up actions or real actions from Laudato Si' activities are "taking part in environmental activities" at 71.4% and "cleaning beaches and rivers" at 35.7%